EFEKTIVITAS LATIHAN KEGEL TERHADAP PENINGKATAN KEPUASAN SEKSUAL PADA AKSEPTOR KB DMPA (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Progestin injection contraception is one of the most widely used and popular hormonal contraceptive options. The use of progestin injection contraception in the long term causes complaints of decreased sexual desire, this is due to high levels of progestin so that the vagina dries up and pain during intercourse. Purpose: To determine the effectiveness of Kegel exercises on increasing sexual satisfaction in DMPA injection acceptors. Method: The research method was designed using a quasi-experimental approach using the one group pre and post-test design approach. The research was conducted in the Sukapakir and Babakan Tarogong Community Health Centers, Bandung City. The number of samples is 20 respondents. Respondents were asked to do Kegel exercises 2 times a day for 2 weeks. Data analysis with Wilcoxon test. Results: The results showed that there was a significant difference in sexual satisfaction before and after being given Kegel exercises with a p value <0.05. Conclusion: Regular Kegel exercises can be recommended to increase sexual satisfaction in DMPA acceptors.